EVALUASI PELAKSANAAN MANAJEMEN BERBASIS SEKOLAH DI SEKOLAH MENENGAH KEJURUAN NEGERI 3 BANTAENG KABUPATEN BANTAENG - Hasmiah . (Makassar Journal of Social Sciences, 2023)
Abstract This study aims to evaluate to what extent the implementation of school-based management in the State Vocational High School 3 Bantaeng., Factors that support and hinder evaluation of the implementation of school-based management in the State Vocational High School 3 Bantaeng. population in this study is principal, teachers, staff, school committee (of the community) with a total of 56 people, In this study, the sample used for the election or census saturated sampling technique, so that the sample in this study is a population which total 56 person. Held data collection techniques for observation, interview and observation and documentation. The results showed that; Application of MBS in Vocational High School 3 Bantaeng at high category, where all indicators supporting MBS have been able to work optimally. Factors that support the implementation of MBS is the managerial ability of high school principals, teachers maximum performance and high levels of education or degree. Factors that inhibit the implementation of MBS is low community participation and income levels are less